2004
DOI: 10.1111/j.1365-2648.2004.03077.x
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of research findings by graduate nurses and midwives

Abstract: It is crucial that some of the major barriers to research utilization are addressed at both individual and organizational levels if evidence-based care is to become a reality. Also, health service managers should consider a number of strategies suggested by respondents to increase the use of research findings in clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
119
0
4

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(136 citation statements)
references
References 49 publications
(142 reference statements)
13
119
0
4
Order By: Relevance
“…However, resistance to the use of SWI was not restricted to medical doctors, but also came from midwives and may reflect a sense of ambivalence towards research and practice change. 16,17 A survey of midwifery and nursing graduates 17 found that more senior practitioners, with a greater degree of autonomy and freedom to practice, would be more likely to adapt their practice to changes in evidence, than less experienced practitioners. This also implies that some practitioners may be constrained by the pressures of heavy workloads, current authoritative knowledge or institutional barriers over the desire to change practice.…”
Section: Discussionmentioning
confidence: 99%
“…However, resistance to the use of SWI was not restricted to medical doctors, but also came from midwives and may reflect a sense of ambivalence towards research and practice change. 16,17 A survey of midwifery and nursing graduates 17 found that more senior practitioners, with a greater degree of autonomy and freedom to practice, would be more likely to adapt their practice to changes in evidence, than less experienced practitioners. This also implies that some practitioners may be constrained by the pressures of heavy workloads, current authoritative knowledge or institutional barriers over the desire to change practice.…”
Section: Discussionmentioning
confidence: 99%
“…Only two individuals used computer-based learning. This reflects that many nurses still feel unsure about how to conduct a literature search (Veeramah 2004) despite the ease of accessing information in the modern world. Knowledge can be acquired from a range of sources: academic programs, study days and conferences, informal contact with specialist practitioners, using the internet (www.ovid.com, www.ncbi.nlm.nih.gov, www.google.com), textbooks (Bennett 1999;Skirton and Patch 2002;Pritchard and Korf 2003;Harper 2004;Lashley 2005) and journals (Skirton and Barnes 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Studies highlight that attitudes towards research are heavily influenced by the work environment in the clinical fields [12] , and also by the individual nurses' interest and knowledge about research and nursing development [13] . Therefore many frameworks and models have been created during recent decades in order to inspire nurses to use research in clinical practice to improve nursing care.…”
Section: Introductionmentioning
confidence: 99%